Bromine monoxide (BrO) measurements made using a MAX-DOAS (Multi-AXis Differential Optical Absorption Spectroscopy) instrument in the austral summer of 2016/17 during the Antarctic Circumnavigation Expedition (ACE). - Benavent, Nuria; Garcia-Nieto, David; Cuevas, Carlos Alberto; Saiz-Lopez, Alfonso (Zenodo, 2020)
Dataset abstract To achieve the objectives of the project, we installed a MAX-DOAS (Multi-AXis Differential Optical Absorption Spectroscopy) instrument on the vessel “Akademik Tryoshnikov”. This instrument is based on the DOAS technique, which is used to measure trace gas concentrations in the atmosphere. The method consists of the analysis of the spectral absorption lines that each trace gas produces in the solar spectra. The DOAS technique uses the narrowband features that every trace gas has in their spectral absorption coefficients. This differential cross section is unique and acts like a fingerprint for the trace gases, allowing to differentiate between them and to estimate their concentrations (for further details see Platt and Stutz, 2008). In the past decades, atmospheric chemists have come to realize that halogen species (like Cl, Br or I and their oxides ClO, BrO and IO) exert a powerful influence on the chemical composition of the troposphere and through that influence affect the evolution of pollutants, hence having a significant impact on climate. These reactive halogen species are potent oxidizers for organic and inorganic compounds throughout the troposphere. In particular, halogen cycles can act on several compounds (such as methane, ozone, particles…), all of which are climate forcing agents through direct and indirect radiative effects. Dynamic exchange of halogens between ocean, sea ice, snowpack and atmosphere is the main driver for the frequent occurrence of Ozone Depletion Events (ODEs) and Atmospheric Mercury Depletion Events (AMDEs) (Saiz-Lopez and von Glasow, 2012). In this dataset we present the mixing ratio and vertical column density of bromine monoxide (BrO) recorded in the austral summer of 2016/2017 in the Southern Ocean and Atlantic Ocean, averaged over one-hour time periods. Dataset contents ace_bromine_monoxide_atmospheric_measurements.csv, data file, comma-separated values data_file_header.txt, metadata, text README.pdf, metadata, PDF/A-1a README.txt, metadata, text Dataset license This dataset of atmospheric bromine monoxide measurements from ACE is made available under the Creative Commons Attribution 4.0 International License (CC BY 4.0) whose full text can be found at https://creativecommons.org/licenses/by/4.0/ : The Antarctic Circumnavigation Expedition (ACE) was made possible by funding from the Swiss Polar Institute and Ferring Pharmaceuticals. Support for the MAX-DOAS installation and data collection was provided by the SORPASSO project (also part of ACE) led by Prof. Rafel Simó. : {"references": ["Cl\u00e9mer, K., Van Roozendael, M., Fayt, C., Hendrick, F., Hermans, C., Pinardi, G., Spurr, R., Wang, P., De Mazi\u00e8re,M., 2010.Multiple wavelength retrieval of tropospheric aerosol optical properties from MAX-DOAS measurements in Beijing. Atmos. Meas. Tech. 3 (4), 863.", "Plane, J.M.C., Saiz-Lopez, A., 2006. UV-Visible Differential Optical Absorption Spectroscopy (DOAS). In: Heard, D.E. (Ed.), Analytical Techniques for Atmospheric Measurement. Blackwell Publishing, Oxford.", "Platt, U., Stutz, J. (2008). Differential Optical Absorption Spectroscopy: Principles and Applications. Springer Berlin Heidelberg, Berlin, Heidelberg, Berlin, Heidelberg.", "Rodgers, C.D. 2000, \"Inverse Methods for Atmospheric Sounding: Theory and Practice\", Singapore: World Scientific Publishing, Singapore.", "Saiz-Lopez, A., & von Glasow, R. (2012). Reactive halogen chemistry in the troposphere. Chemical Society Reviews. https://doi.org/10.1039/c2cs35208g", "Benavent, Nuria, Garcia-Nieto, David, Cuevas, Carlos Alberto, & Saiz-Lopez, Alfonso. (2020). Raw spectra measurements of scattered sunlight collected using a MAX-DOAS (Multi-Axis Differential Optical Absorption Spectroscopy) instrument in the austral summer of 2016/17 during the Antarctic Circumnavigation Expedition (ACE). (Version 1.0) [Data set]. Zenodo. http://doi.org/10.5281/zenodo.3827443", "Benavent, Nuria, Garcia-Nieto, David, Cuevas, Carlos Alberto, & Saiz-Lopez, Alfonso. (2020). Sky images recorded during the austral summer of 2016/17 as part of the Antarctic Circumnavigation Expedition (ACE). (Version 1.0) [Data set]. Zenodo. http://doi.org/10.5281/zenodo.3827445"]}